The Usage of Terms “kūrybiškumas” and “kūrybingumas” in the Scientific Publications of Lithuanian Authors, and Analysis of Meaningful Differences of the Words - Beresnevičius, Gediminas (Psichologija, 2022)
The Lithuanian scientific community has not yet reached a decision which Lithuanian word, “kūrybiškumas” or “kūrybingumas” (both translated into English as “creativity“), is more suitable for use in the creative psychology, educology and other domains. This article defines the words “kūrybiškumas” and “kūrybingumas” as the acquired abilities of the creative subject to manifest new material and ideal objects. In addition, the two words are described as a property or characteristic of the product of activity and of the environment.The author reviews the usage of terms “kūrybiškumas” and “kūrybingumas” in the scientific publications of Lithuanian authors, and analyzes meaningful differences of the words. The quantitative research assesses all the publications in Lithuanian language which contain at least one of the terms in their titles and which were published between 1979 and 2019. During this period, 400 scientists submitted 426 publications which meet the previously mentioned criteria.It was found that the term “kūrybiškumas” is accepted by the majority of the Lithuanian researchers (80.75%). This word is found in 76.76% of publication titles and 68.08% of texts.The analysis of publications revealed that the meaningful difference between the words “kūrybiškumas” and “kūrybingumas” can be doubted, therefore the meaning of the two terms is the same. Both words (“kūrybiškumas” and “kūrybingumas”) can be used to describe the creator, the creation process, the work or the result, and the environment. The term “kūrybiškumas” is broader and the meaning is somewhat wider than that of the term “kūrybingumas”.In order to avoid the confusion related to the use of the two terms, the author suggests to use only the word “kūrybiškumas”. Alternatively, the terms “kūrybiškumas” and “kūrybingumas” should be considered as synonyms.
Keywords: kūrybiškumas; kūrybingumas; Lithuanian author publications; creativity; meaning analysis; synonym analysis